Homozygous EXOSC3 mutation c.92G→C, p.G31A is a founder mutation causing severe pontocerebellar hypoplasia type 1 among the Czech Roma - Schwabova, Jaroslava; Brozkova, Dana Safka; Petrak, Borivoj; Mojzisova, Mahulena; Pavlickova, Klara; Haberlova, Jana; Mrazkova, Lenka; Hedvicakova, Petra; Hornofova, Ludmila; Kaluzova, Marie; Fencl, Filip; Krutova, Marcela; et al. (Journal of neurogenetics, 2013)
Pontocerebellar hypoplasia type 1 (PCH1) is characterized by cerebellar and anterior horn motor neuron degeneration and loss, signs of spinal muscular atrophy plus. Patients manifest severe perinatal weakness, hypotonia, and respiratory insufficiency, causing death frequently before the age of 1 year. Recently, causative mutations in EXOSC3 were reported in a majority of PCH1 patients, but the detailed clinical phenotype caused by EXOSC3 mutations, genotype-phenotype correlations, and prevalent mutations in specific ethnic groups is not yet known. Three unrelated Czech Roma patients with PCH1 were investigated clinically, electrophysiologically, neuroradiologically, and neuropathologically (patients 1 and 2). The entire coding region of the EXOSC3 gene, including the adjacent intron sequences, was sequenced in all three patients. The same mutation c.92G→C, p.G31A in EXOSC3 was found in all three affected patients in homozygous state and in heterozygous state in the parents from two of the families. Haplotype analysis with four flanking microsatellite markers showed identical haplotype in 9 out of 11 haplotypes carrying the c.92G→C, p.G31A mutation. Furthermore, four heterozygotes for this mutation were found in anonymous DNA samples from 90 unrelated Roma individuals. All four of these samples shared the same haplotype. No heterozygous sample was found among 120 anonymous DNA samples from Czech non-Roma individuals with no familial relation. It may therefore be concluded that EXOSC3 c.92G→C, p.G31A mutation is a founder mutation with high prevalence among the Czech Roma causing a similar and particularly severe phenotype of PCH1. These observations from the Czech Roma may have consequences also for other Roma from other countries. PCH1 caused by EXOSC3 founder mutation c.92G→C, p.G31A extends the list of autosomal recessive disorders rare among the general population but more frequent among Roma at least in the Czech Republic.
Keywords: olivopontocerebelární atrofie; Homozygote; Olivopontocerebellar Atrophies; kojenec; Česká republika; Haplotypes; mužské pohlaví; Exosome Multienzyme Ribonuclease Complex; mutace; Infant; fenotyp; RNA-Binding Proteins; Czech Republic; Romové; exozom; polymerázová řetězová reakce s reverzní transkripcí; Infant, Newborn; Phenotype; ženské pohlaví; novorozenec; Mutation; Humans; proteiny vázající RNA; haplotypy; homozygot; Roma; Reverse Transcriptase Polymerase Chain Reaction; Female; lidé; Male